Effects of anthropogenic activities on long-term changes of nitrogen budget in a plain river network region: A case study in the Taihu Basin - Huishu, Lian; Qiuliang, Lei; Xinyu, Zhang; Haw, Yen; Hongyuan, Wang; Limei, Zhai; Hongbin, Liu; Huang, Jr-Chuan; Tianzhi, Ren; Jiaogen, Zhou; Weiwen, Qiu (The Science of the total environment, 2018)
Over recent decades, Taihu Lake, the third largest freshwater lake in China, has borne the brunt of intensive human activities. Non-point source pollutants and discharges of domestic wastewater are now the main cause of eutrophication. To control non-point source pollution, it is useful to have a good understanding of the spatial and temporal distribution of N (nitrogen). In this study, we applied Export Coefficient Model (ECM) and the Net Anthropogenic Nitrogen Inputs (NANI) method to estimate the N loads in the Taihu Basin at county scale since 1980. We found that N inputs and exports had increased from 6432 and 3170 kg N km−2 yr−1 in 1980 to 9722 and 4582 kg N km−2 yr−1 in 2010, respectively. The 151% increase of N inputs, but 144% increase of riverine N outputs suggested the more N was retained within the Taihu Basin. Both the population density and the urban areas were strongly correlated with N inputs and exports. Approximately 38% of the N inputs were exported in 2010, but only 19% were exported in 1980. This ratio illustrated that human activities, especially urbanization and population growth, have upset N budget in the Taihu Basin. This study supported by empirical models provides a case to demonstrate the N cascade in the Taihu Basin and can also be used to support decision making and to facilitate the development of measures to control N in the future. [Display omitted] •Both inputs and exports of N increased substantially during the study period.•The NANI method and the ECM are first integrated to assess N load in a basin.•Urbanization, economic/population growth are key factors of spatial-temporal changes.•The contribution of agricultural source to N exports was decreased.•Destruction of the N balance of the ecosystem is investigated in the Taihu Basin, China.